1998
DOI: 10.1038/sj.bmt.1701538
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter exchange by guidewire for treatment of catheter-related bacteraemia in patients undergoing BMT or intensive chemotherapy

Abstract: Summary:Current guidelines for the treatment of catheter-related bacteraemia (CRB) advise against central venous catheter (CVC) exchange because of the potential risk of prolonging infection. However, there are no consistent data proving this recommendation. We evaluated prospectively the usefulness of CVC exchange by guidewire for the treatment of CRB in patients undergoing BMT or intensive chemotherapy. CVC exchange was considered when fever and positive blood cultures persisted after 2 days of adequate anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Microbiologic data suggestive of true CRBSI caused by potential skin flora rather than contamination include the following: multiple blood samples with positive culture results obtained from different sites; quantitative blood cultures performed on samples drawn from a catheter with growth of >15 cfu/mL of blood or isolation of the same organism from a catheter culture and a percutaneous blood culture, especially if a culture performed on blood drawn from the catheter shows growth at least 2 h earlier than a culture performed on blood drawn from a peripheral vein [72]. Although several studies suggest that catheter exchange over a guidewire can be used successfully to manage CRBSI associated with long-term catheters [73], most of these were small, uncontrolled studies with poor definitions, and none of these studies used antimicrobial catheters as a replacement for the infected catheter [7377]. Management of CRBSI for patients with a long-term CVC or implantable device is summarized in tables 5 and 6 and in figure 2.…”
Section: Guideline Recommendations For the Management Of Intravasculamentioning
confidence: 99%
“…Microbiologic data suggestive of true CRBSI caused by potential skin flora rather than contamination include the following: multiple blood samples with positive culture results obtained from different sites; quantitative blood cultures performed on samples drawn from a catheter with growth of >15 cfu/mL of blood or isolation of the same organism from a catheter culture and a percutaneous blood culture, especially if a culture performed on blood drawn from the catheter shows growth at least 2 h earlier than a culture performed on blood drawn from a peripheral vein [72]. Although several studies suggest that catheter exchange over a guidewire can be used successfully to manage CRBSI associated with long-term catheters [73], most of these were small, uncontrolled studies with poor definitions, and none of these studies used antimicrobial catheters as a replacement for the infected catheter [7377]. Management of CRBSI for patients with a long-term CVC or implantable device is summarized in tables 5 and 6 and in figure 2.…”
Section: Guideline Recommendations For the Management Of Intravasculamentioning
confidence: 99%
“…Another option to consider is changing the CVC over a guidewire instead of removing it and replacing it with a new CVC at a new site. In the absence of exit-site infections, this approach seems to be safe and effective in adult HD patients (even in the presence of sepsis) as long as antibiotic therapy has been started [34,74,75,76,77,78,79]; however, there are no data concerning children on HD.…”
Section: Catheter Replacementmentioning
confidence: 99%
“…Most of the publications that describe GCE results are from the adult literature for patients on total parenteral nutrition, chronic hemodialysis patients, burn patients, and intensive care unit patients . Castelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Catheter‐related complications, such as malfunction and displacement, and patient/family preferences are also indications for GCE. Different studies performed in adult populations have suggested that GCE is associated with a low complication rate and without an increased risk of infection . However, these findings have not been confirmed in children with malignancies.…”
Section: Introductionmentioning
confidence: 91%